Herder-related violence, labor allocation, and the gendered response of agricultural households - Bloem, Jeffrey R.; Damon, Amy; Francis, David C.; Mitchell, Harrison (Elsevier, 2025)
Violent conflict between nomadic herders and settled agricultural communities in Nigeria occurs as both groups clash over the use of land and natural resources, in part, due to a changing climate. We generate theory and evidence to study the labor responses of individuals within agricultural households to herder-related violence and consider a “shadow of violence” mechanism, whereby previous exposure to a violent event alters labor responses to a recent event. Using panel data from 2010 through 2019, we highlight how exposure to violence can lead to differing responses in the planting or harvest seasons and among men or women. In the planting season, among both men and women living in households with no previous exposure to herder-related violence, we find that exposure (i.e., singular exposure) leads to a reduction in household enterprise work, but among households with previous exposure experience, exposure (i.e., repeated exposure) leads to an increase in household enterprise work. Meanwhile, repeated exposure to herder-related violence reduces agricultural work among men only. This leads total hours worked to decline in response to singular exposure and to increase in response to repeated exposure especially among women. In the harvest season, we find that singular exposure increases agricultural work among both men and women, but repeated exposure reduces agricultural work among men only.